Dormant phages of Helicobacter pylori reveal distinct populations in Europe - Vale, F.F.; Vadivelu, J.; Oleastro, M.; Breurec, S.; Engstrand, L.; Perets, T.T.; Mégraud, F.; Lehours, P. (Nature Research, 2015)
Prophages of Helicobacter pylori, a bacterium known to co-evolve in the stomach of its human host, were recently identified. However, their role in the diversity of H. pylori strains is unknown. We demonstrate here and for the first time that the diversity of the prophage genes offers the ability to distinguish between European populations, and that H. pylori prophages and their host bacteria share a complex evolutionary history. By comparing the phylogenetic trees of two prophage genes (integrase and holin) and the multilocus sequence typing (MLST)-based data obtained for seven housekeeping genes, we observed that the majority of the strains belong to the same phylogeographic group in both trees. Furthermore, we found that the Bayesian analysis of the population structure of the prophage genes identified two H. pylori European populations, hpNEurope and hpSWEurope, while the MLST sequences identified one European population, hpEurope. The population structure analysis of H. pylori prophages was even more discriminative than the traditional MLST-based method for the European population. Prophages are new players to be considered not only to show the diversity of H. pylori strains but also to more sharply define human populations.